Ranking and the Globalization of Higher Education - Smith, Peter (Humanities, Arts and Social Sciences Studies, 2013)
Since the 1980s, the idea of ranking universities has become increasingly widespread. Originating in national rankings systems in the USA, the rankings movement has become international. This paper examines the varied indices of university excellence that are employed in the main rankings systems; asks how valid they are as measures of university quality and the reasons they have become so popular; identifies the ways in which they exhibit systematic bias and the various consequences they have for academic life; describes the emergence of ananti-rankings movement in American universities; and suggests various ways in which universities may respond to rankings in the future. A paper presented to a conference on ‘University Excellence andthe Liberal Arts Tradition’, organized by the Social Science Division, Mahidol University International College, Mahidol University, Thailand, on 27 May 2011. My thanks to Ilyas Baker and Christian Osterheld for their comments on an earlier draft of this paper.The academic world has experienced a number of profound changes over the past couple of decades, making the experiences of teaching and learning at most universities significantly different now than they were in the period up to about the 1980s. Four major changes of particular importance have been: (i) the enormous expansion of higher education, especially in terms of student numbers, but also in the numberof colleges; (ii) the growing impact of ‘academic capitalism’ and the‘audit culture’; (iii) the recent focus – some would say obsession – with university rankings and branding; and (iv) the increasing impact of ‘internationalization’ and ‘globalization’. The present paper will examine aspects of this third theme, and subsequent papers will examine the other three.